Earned Value Method Management Applied to The Construction of The Multifamily Building – Lima, Peru 2020 - HERNANDEZ, FRANZ; ESENARRO, DORIS; RODRIGUEZ, CIRO; VELA, LORENA; CALVO, ROBERT (The journal of contemporary issues in business and government, 2021)
This research aims to assess costs and time in the study of the earned value method management applied to the construction of the multifamily building in Lima, it is worth mentioning that the main problem of low productivity rates is the low cost control, that affects directly the performance of projects. The methodology used in this context is the earned value, which allows managing the costs and time of projects, gaining as a result the S curve and the control table, as a conclusion it could be said that the companies should maintein a correct control of time and cost of projects, because as it can be seen, at the end of the project, the company will have a lost of money for S/ 134,176.33 soles from month 06, which represents the 1.94% at the end of the Project.